Microbes Thriving in Extreme Environments: How Do They Do It? - Jha, Prameela (International Journal of Applied Sciences and Biotechnology, 2014)
Our knowledge about habitat of microorganisms appears diminutive when we witness amazing flexibility in choice of survival under various conditions. Extremophiles refers to the organisms living and carrying out vital life processes at extreme conditions of temperature, pressure, pH, salt concentration among others and this is why they have attracted attention of researchers worldwide. There is a continuous quest to unreveal the probable mechanism or structural and functional adaptations that make extremophiles survive under other holistic conditions. There occur modifications primarily in cell membrane, DNA, RNA, protein and enzymes in order to render fit microbial cell to its external environment. Thus, extremophiles are robust source of high temperature and alkali stable enzymes. Various enzymes as lipase and protease have found several applications in food and cosmetic industry while Taq polymerase from bacteria Thermus aquaticus has revolutionized entire scene of molecular biology. Present review focuses on extremophiles, their structural and molecular adaptations to overcome unfavorable conditions of environment. DOI: http://dx.doi.org/10.3126/ijasbt.v2i4.10543 Int J Appl Sci Biotechnol, Vol. 2(4): 393-401